Total Synthesis of Lagerstannin C: Follow-up of the Khanbabaee’s Synthesis - Kaneko, Yuki; Wakamori, Shinnosuke; Ikeuchi, Kazutada; Ohara, Kenya; Tanaka, Takashi; Yamada, Hidetoshi (Synthesis, 2017)
This report describes the total synthesis of lagerstannin C, a natural ellagitannin that has d-gluconic acid in the molecule. The study presented here is the first synthesis of the gluconic acid containing ellagitannin. The key step in the synthesis is the opening of δ-lactone through transesterification to form the corresponding benzyl ester.
Keywords: total synthesis; natural products; ellagitannin; lagerstannin C; gluconic acid; transesterification